1982
DOI: 10.1016/0033-5894(82)90048-5
|View full text |Cite
|
Sign up to set email alerts
|

Paleoceanography of Surface Waters in the Gulf of Mexico during the Late Quaternary

Abstract: Late Quaternary paleotemperatures and paleosalinities of surface waters of the Gulf of Mexico were estimated using a multivariate statistical analysis of census data of planktonic foraminifera. Two climatic extremes were selected for detailed basinwide study, the climatic optimum 125,000 yr ago and the glacial maximum 18,000 yr ago. In addition, patterns of climatic change were examined in seven piston cores from 127,000 yr ago to the present day. During the climatic optimum 125,000 yr ago temperature distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
29
0

Year Published

1984
1984
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 30 publications
2
29
0
Order By: Relevance
“…The foraminifer assemblages show clear differences between older and younger parts of the Holocene. The warmest surface-water temperatures, as indicated by high relative abundances of Pulleniatina obliquiloculata and G. menardii [20], occurred at about 5 ka, which is consistent with the results of Brunner (1982) [7]. [21] summarized census data on foraminifer assemblages in several cores from the western and northern GOM, spanning most of the Holocene, and concluded that the relative abundance of the G. sacculifer in GOM foraminiferal assemblages is a reliable proxy for changes in the average position of the ITCZ.…”
Section: Holocene Climate Trends and Variabilitysupporting
confidence: 80%
See 3 more Smart Citations
“…The foraminifer assemblages show clear differences between older and younger parts of the Holocene. The warmest surface-water temperatures, as indicated by high relative abundances of Pulleniatina obliquiloculata and G. menardii [20], occurred at about 5 ka, which is consistent with the results of Brunner (1982) [7]. [21] summarized census data on foraminifer assemblages in several cores from the western and northern GOM, spanning most of the Holocene, and concluded that the relative abundance of the G. sacculifer in GOM foraminiferal assemblages is a reliable proxy for changes in the average position of the ITCZ.…”
Section: Holocene Climate Trends and Variabilitysupporting
confidence: 80%
“…Malmgren and Kennett [16] used principal component analysis of foraminiferal-assemblage data from a series of cores in the western GOM to develop qualitative estimates of SST changes through the Holocene. Brunner [7] used the transfer function technique of Imbrie and Kipp [17] to estimate SSTs and salinities extending back through the last interglacial in several cores from the GOM. The sampling strategy of Brunner [7] was designed to establish the glacial-interglacial signal and includes only a few SST estimates for the Holocene.…”
Section: Holocene Climate Trends and Variabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…The processing technique is standard but differences between the labs are noted below. Additional information regarding methodology can be found in Imbrie &Kipp (1971), Brunner andCooley (1976), Brunner (1979Brunner ( , 1982, and Dowsett & Poore (2001). Careful attention was paid to the taxonomic concepts of the various authors so that the resulting data set is internally taxonomically-consistent.…”
mentioning
confidence: 99%